2012
DOI: 10.1371/journal.pgen.1002512
|View full text |Cite
|
Sign up to set email alerts
|

EMF1 and PRC2 Cooperate to Repress Key Regulators of Arabidopsis Development

Abstract: EMBRYONIC FLOWER1 (EMF1) is a plant-specific gene crucial to Arabidopsis vegetative development. Loss of function mutants in the EMF1 gene mimic the phenotype caused by mutations in Polycomb Group protein (PcG) genes, which encode epigenetic repressors that regulate many aspects of eukaryotic development. In Arabidopsis, Polycomb Repressor Complex 2 (PRC2), made of PcG proteins, catalyzes trimethylation of lysine 27 on histone H3 (H3K27me3) and PRC1-like proteins catalyze H2AK119 ubiquitination. Despite functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
166
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(174 citation statements)
references
References 83 publications
(152 reference statements)
8
166
0
Order By: Relevance
“…Consistent with the misexpression of FLC, MAF4, and MAF5 in the mutants, it has been shown previously that the levels of H3K27me3 marks at these genes were altered in PRC2 mutants (Jiang et al, 2008), emf1, and atring1a (Kim et al, 2012b;Shen et al, 2014). Therefore, to investigate whether AtBMI1 loss of function also affected the levels of H3K27me3 marks at FLC, MAF4, and MAF5, we examined the levels of this histone modification in atbmi1a/b mutants at the first intron of the genes, which has been shown to display an enrichment of H3K27me3 marks in wild-type seedlings at 9 to 10 DAG (Shen et al, 2014; Fig.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…Consistent with the misexpression of FLC, MAF4, and MAF5 in the mutants, it has been shown previously that the levels of H3K27me3 marks at these genes were altered in PRC2 mutants (Jiang et al, 2008), emf1, and atring1a (Kim et al, 2012b;Shen et al, 2014). Therefore, to investigate whether AtBMI1 loss of function also affected the levels of H3K27me3 marks at FLC, MAF4, and MAF5, we examined the levels of this histone modification in atbmi1a/b mutants at the first intron of the genes, which has been shown to display an enrichment of H3K27me3 marks in wild-type seedlings at 9 to 10 DAG (Shen et al, 2014; Fig.…”
Section: Resultssupporting
confidence: 84%
“…Recent findings regarding the PcG mechanism have shown that PRC1 is required for H3K27me3 marking at some target genes in both Arabidopsis (Yang et al, 2013a;Calonje, 2014) and animals (Comet and Helin, 2014;Schwartz and Pirrotta, 2014), placing PRC1 in a decisive position for the repression of some genes. In addition, several lines of evidence have suggested the existence of different mechanisms for PRC1-mediated repression in Arabidopsis (Kim et al, 2012b;Yang et al, 2013a;Calonje, 2014); however, it is not known whether a combination of different PRC1 subunits is required to exert the different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Genomewide investigation of EMF1 targets has revealed that EMF1 mediates gene expression via diverse mechanisms. It acts along with PRC2 to repress the flower MADS box genes as well as with PRC1 to regulate the expression of many other genes (Kim et al, 2012).…”
mentioning
confidence: 99%